In loco nursing practice inspection costs in a Brazilian setting - Vera Lucia de Souza Alves; Antônio Fernandes Costa Lima (SciELO, 2022)
Abstract Objective: To identify the average direct cost related to the direct labor of the inspectors involved in the "in loco inspection" step of the inspection process carried out at the Headquarters of the Regional Nursing Council of São Paulo. Method: Quantitative, exploratory-descriptive research, in the form of a single case study. The non-probabilistic convenience sample consisted of records of initial and return "in loco inspections", carried out by inspectors working at the Headquarters of The Regional Nursing Council of São Paulo, from January 13, 2020 to March 13, 2020. Results: The average direct cost of initial in loco inspection (N = 182) corresponded to BRL 331.67 (SD = 140.32), ranging from BRL 115.80 to BRL 1071.15, and that of return in loco inspection (N = 98) to BRL 256.16 (SD = 130.90), ranging from BRL 77.20 to BRL 694.80. Time and cost variables analysis of initial and return in loco inspections showed an alpha significance level of 0.05, and it was possible to statistically state that the time (p ≤ 0.001) and the cost of initial in loco inspection (p ≤ 0.001) are higher than those for return in loco inspection. Conclusion: the cost of the step of "in loco inspection" will support the Nursing Council in the decision-making process aiming at allocating efficiency of human resources required in the inspection process.